2006
DOI: 10.1016/j.jretai.2006.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Private label positioning: Quality versus feature differentiation from the national brand

Abstract: This paper investigates the retailer's problem of positioning her private label against two national brands in terms of both product quality and product features. Using a demand function derived from consumer utility, we show that the private label's best positioning strategy depends on the nature of the national brands' competition and its own quality. When the national brands are differentiated, a high quality private label should position closer to a stronger national brand, and a low quality private label … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(41 citation statements)
references
References 17 publications
1
40
0
Order By: Relevance
“…With private label brands consistently emphasising their quality similarity with national brands, it may affect the smart‐shopper self‐perceptions of those consumers who are oriented towards private label brands, as these consumers are provided with an advantageous purchase opportunity for a lower price. Chan Choi and Coughlan () reported waning loyalty among consumers towards national brands. On the other hand, Ailawadi et al .…”
Section: Conceptual Framework and Hypothesis Developmentmentioning
confidence: 99%
“…With private label brands consistently emphasising their quality similarity with national brands, it may affect the smart‐shopper self‐perceptions of those consumers who are oriented towards private label brands, as these consumers are provided with an advantageous purchase opportunity for a lower price. Chan Choi and Coughlan () reported waning loyalty among consumers towards national brands. On the other hand, Ailawadi et al .…”
Section: Conceptual Framework and Hypothesis Developmentmentioning
confidence: 99%
“…Since the mid 1990s many retailers have repositioned their own brands to bring them up to a standard where they can challenge manufacturers' brands (Choi, Coughlan 2006). For example, UK retailers started to enhance their premium own brand ranges.…”
Section: Perceived Qualitymentioning
confidence: 99%
“…Initial studies have found that a retailer's introduction of a store brand product can be viewed as its resource use for additional marketing strategies such as store differentiation, store loyalty, or store profitability. More recently, studies have shown that retailers who offer store brands set a quality of their store brands very close to the quality of leading national brands in terms of product characteristics because of its strategic relationship with the national brand [2][3][4][5][6]. Retailers have to make two positioning decisions, namely, horizontal and vertical positioning.…”
Section: Introductionmentioning
confidence: 99%